Hepatocellular carcinoma metastasis to salivary glands: a systematic review of diagnostic challenges and survival outcomes - Morada, Anthony Onde; Chen, Caroline Kai; Akateh, Clifford; Marvin, Michael R.; Kotru, Anil (Journal of Gastrointestinal Oncology, 2026)
Background: Hepatocellular carcinoma (HCC) metastasizes predominantly to the lungs, lymph nodes, and bone; salivary gland involvement is exceedingly rare and poorly characterized. We conducted a systematic review to define the clinical profile, diagnostic challenges, and outcomes of this unusual metastatic pattern.Methods: Following PRISMA 2020 guidelines with prospective protocol registration (PROSPERO CRD42024559907), we searched six databases from inception through November 2024 for pathologically confirmed HCC salivary gland metastasis. Two reviewers independently screened records, extracted patient-level data, and appraised study quality. Outcomes were summarized using descriptive statistics and Kaplan-Meier survival analysis.Results: From 148 records, eight published cases met inclusion criteria; combined with one institutional case, the final cohort comprised nine patients [1998–2024]. All were male (median age 64 years; range, 36–82 years). Alcohol use disorder (55.6%) and diabetes mellitus (33.3%) were the most common comorbidities. The parotid gland was affected in 88.9% of cases. Two-thirds of cases presented synchronously with primary HCC; among three metachronous cases, the median interval to salivary metastasis was 2.5 years, including one case arising after liver transplantation. Initial fine-needle aspiration biopsy (FNAB) was diagnostic in only 2 of 8 attempted cases (25%); 4 of 8 ultimately required surgical biopsy. Among seven patients with survival data, median overall survival was 6 months (range, 2–24 months). Patients undergoing surgical resection had numerically longer median survival (12 vs. 5 months); no formal statistical comparison was performed given the small sample size.Conclusions: HCC salivary gland metastasis has been observed exclusively in males across all reported cases, with strong parotid predilection and poor prognosis. FNAB has a low diagnostic yield, and early surgical biopsy should be considered when clinical suspicion is high. Delayed metastases, including post-transplantation, underscore the need for extended surveillance and sustained clinical vigilance in HCC follow-up.